Chemical looping gasification of lignin with bimetallic oxygen carriers. (February 2020) - Wu, Jingli; Bai, Lei; Tian, Hanjing; Riley, Jarrett; Siriwardane, Ranjani; Wang, Zhiqi; He, Tao; Li, Jianqing; Zhang, Jinzhi; Wu, Jinhu
Highlights: BaFe2 O4 demonstrated the best ability to selectively gasify lignin and with a high syngas production. Four bimetallic oxygen carriers (CaFe2 O4, CaMn2 O4, BaFe2 O4 and BaMn2 O4 ) showed the ability to be fully regenerated in air after reduction. CO2 enhances the gasification process with these oxygen carriers. Bimetallic oxygen carriers accelerated the kinetics of gasification process. Abstract: Chemical Looping Gasification (CLG) is a promising technology to produce syngas from renewable biomass material without the need for upstream air separation. It has been proposed as an innovative scheme for eliminating the tar through hot gas cleaning after biomass is gasified. Lignin is the main component of biomass and the second-most abundant organic material on the planet. Also, lignin is a waste by-product from integrated bio-refineries. Four bimetallic oxygen carriers (CaFe2 O4, CaMn2 O4, BaFe2 O4 and BaMn2 O4 ) are systemically studied for CLG of biomass-based lignin as fuel source. Based on thermodynamic analysis and online mass spectral data, BaFe2 O4 demonstrated the best ability to selectively gasify lignin and had good regeneration, which made it very attractive for potential chemical looping partial oxidation of biomass in commercial applications. All oxygen carriers studied showed the ability to be fully regenerated in the air after reduction. Adding CO2 increased production of CO due to reverse Boudouard reaction (C + CO2 = 2CO) and accelerated both biomass conversion and reaction kinetics of the gasification process in the presence of these bimetallic oxygen carriers.